Regime complexity and expertise in transnational governance: Strategizing in the face of regulatory uncertainty - Sigrid Quack (Oñati Socio-Legal Series)
The rise and spread of transnational governance arrangements has added to the legal indeterminacy of existing regime complexes. The combined regulatory uncertainty resulting from international regime complexes and transnational polycentric governance heightens the role of expertise in managing this institutional complexity. The rising importance of knowledgeable actors with claims to policy-relevant expertise, according to many scholars, is expected further to advantage well-resourced and powerful actors. However, attention to recent developments in accounting and copyright, as two transnational governance fields that have been dominated by a small group of powerful actors for more than three decades, sheds doubt on the generalizability of such arguments. Although representing least likely cases for change, the empirical evidence presented in this paper shows how apparently weak or marginalized actors – whether they are part of public bureaucracies or civil society – developed expertise-based strategies to claim greater involvement and influence in rule and standard-setting. Their strategizing on regime complexity opened up previously shielded policy spaces to broader audiences, thereby transforming actor constellations, preferences and problem definitions in the two policy fields. These findings suggest that under conditions of complexity, indeterminacy and uncertainty, claims to expertise-based rule are becoming increasingly contested – even in transnational governance fields that have a long-established trajectory of rule-setting and rule-implementation monopolized by small groups of professionals, industrialists or technical diplomats.